A razão pública legitimadora do estado democrático constitucional a luz da teoria da justiça de John Rawls - Leão, Cristine Madeira Mariano (2015)
The author writes about the attributions of public reason in John Rawls's theory of justice, in particular, its compelling link function which submits the basic institutions of society, especially, public institutions. Maintains that the observation of public reason is a condition that legitimates the exercice of public authority, which must conform to the formal and material limits that justify citizen's reason, with the aim of achieving the conception of justice.